2007
DOI: 10.1111/j.1399-3054.2007.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking leaf chlorophyll fluorescence properties to physiological responses for detection of salt and drought stress in coastal plant species

Abstract: Effects of salinity and drought on physiology and chlorophyll fluorescence were used to evaluate stress in two coastal plants, Myrica cerifera (L.) and Phragmites australis (Cav.) Trin. ex Steud. Drought and salinity stress were induced and measurements of stomatal conductance, photosynthesis, xylem pressure potential (psi) and fluorescence were conducted following treatment. The onset of stress began at 2 g l(-1) for M. cerifera, and 5 g l(-1) for P. australis, as seen by significant decreases in physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 44 publications
8
41
0
3
Order By: Relevance
“…In our study, F v /F m measured at T1 and T2 did not show significant differences between control and stress treatments (data not shown). Other studies showed little or no effect on F v /F m (Lee et al 2004;Naumann et al 2007;Niu et al 2010;) even when leaf growth and gas exchange were reduced. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, F v /F m measured at T1 and T2 did not show significant differences between control and stress treatments (data not shown). Other studies showed little or no effect on F v /F m (Lee et al 2004;Naumann et al 2007;Niu et al 2010;) even when leaf growth and gas exchange were reduced. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The ChlF signal can provide critical information about the growth status of plants, and therefore it has been used as an effective tool to monitor plant stress induced by air pollution [25,26], water deficit [28,29], herbicide treatment [2], and salt and drought [30]. Quantitative estimation of the fluorescence parameters for crop leaves would be of high importance in assessing the photosynthetic rates of green plants and monitoring the stress conditions of crops.…”
Section: Potential and Limitations Of Applying Model Inversion For Thmentioning
confidence: 99%
“…Se trata de un méto-do no destructivo y muy sensible, capaz de detectar alteraciones en la etapa fotoquímica, antes de que la planta muestre síntomas visibles (Naumann, Young & Anderson, 2007).…”
Section: Introductionunclassified